2007
DOI: 10.1002/ar.20630
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Klotho Protein in Dentin Formation and Mineralization

Abstract: Klotho-deficient mice exhibit multiple pathological conditions resembling human aging. Our previous study showed alterations in the distribution of osteocytes and in the bone matrix synthesis in klotho-deficient mice. Although the bone and tooth share morphological features such as mineralization processes and components of the extracellular matrix, little information is available on how klotho deletion influences tooth formation. The present study aimed to elucidate the altered histology of incisors of klotho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…14,15 Similarly, a dystrophic pulp calcification, root dilaceration, and a thistle shaped pulp have been reported in the tumoral calcinosis patients who are deficient in FGF23 and have increased phosphate levels. 31,32 This ectopic ossification is linked to an increase in apoptosis of the odontoblasts.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…14,15 Similarly, a dystrophic pulp calcification, root dilaceration, and a thistle shaped pulp have been reported in the tumoral calcinosis patients who are deficient in FGF23 and have increased phosphate levels. 31,32 This ectopic ossification is linked to an increase in apoptosis of the odontoblasts.…”
Section: Discussionmentioning
confidence: 87%
“…11,13 Both Fgf23- null and Klotho -deficient mice are reported to have mild dentin malformation and increased apoptosis in odontoblasts, which is due to a high phosphate level. 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, osteoblasts show an impairment in the expression of alkaline phosphatase and the ability to form mineralized nodules [13,14]. Histological studies have also revealed some abnormalities in osteoid and dentin mineralization [15,16]. The impaired osteoclastogenesis appears to be associated with an up-regulation of osteoprotegerin synthesis, an inhibitor of osteoclast precursor differentiation, and indeed it is partially rescued by deleting the osteoprotegerin gene [17].…”
Section: Klotho and Bonementioning
confidence: 93%
“…Klotho functions as an aging-suppressor and has been reported to be a regulator of oxidative stress and senescence [86]; in fact, loss of klotho leads to enhanced apoptosis in odontoblasts and disturbed mineralization in teeth [87]. In contrast to what had been described originally [81], it has been shown more recently by micro-CT that, in 3-month-old klotho-/-mice, trabecular bone mass at the tibia actually increases over wild type littermates [88].…”
Section: The Klotho-deficient Mouse: a Model Of Disrupted Osteoblastsmentioning
confidence: 96%